Metabolism and excretion of 5-ethyl-2-{5-[4-(2-hydroxyethyl)piperazine-1-sulfonyl]-2-propoxyphenyl}- 7-propyl-3,5-dihydropyrrolo[3,2-d]-pyrimidin-4-one (SK3530) in rats - Lee, Jaeick; Yoo, Hye Hyun; Rhim, Kwang Jin; Sohn, Dong-Ryul; Kim, Dong-Hyun (WILEY, 2007)
The in vitro and in vivo metabolism of a novel PDE 5 inhibitor, SK3530, was investigated in rats. Bile, plasma, feces, urine and liver samples were collected and analyzed using a high-performance liquid chromatography (HPLC) system equipped with ultraviolet (UV), mass spectrometric and radioactivity detectors. After a single oral administration, the mean radiocarbon recovery was 92.32 +/- 6.26%, with 91.25 +/- 6.25 and 1.07 +/- 0.21% in the feces and urine, respectively. The biliary excretion of radioactivity for the first 24 h period was approximately 38.82%, suggesting that SK3530 is cleared by hepatobiliary excretion. In vitro incubation of SK3530 with rat and human liver microsomes resulted in the formation of twelve and ten metabolites, respectively. SK3530 was extensively metabolized to twenty different metabolites, including three glucuronide and three sulfate conjugates in rats. The structures of these metabolites were elucidated based on MSn spectral analyses. Six major metabolic pathways were identified in the rat: N-dealkylation and oxidation of the hydroxyethyl moiety; N,N-deethylation and hydroxylation of the piperazine ring; hydroxylation of the propyl group and sulfate conjugation. An additional metabolite due to aromatic hydroxylation was also identified in hepatic microsomes. Copyright (c) 2007 John Wiley & Sons, Ltd.
Keywords: COLLISION-INDUCED DISSOCIATION; MASS-SPECTROMETRY; IN-VITRO; SILDENAFIL; DRUG; IONIZATION; DA-8159